2021
DOI: 10.1021/acs.molpharmaceut.0c00960
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Electrostatics for the Interaction of Tyrosine Hydroxylase with Porous Silicon Nanoparticles

Abstract: Tyrosine hydroxylase (TH) is the enzyme catalyzing the rate-limiting step in the synthesis of dopamine in the brain. Developing enzyme replacement therapies using TH could therefore be beneficial to patient groups with dopamine deficiency, and the use of nanocarriers that cross the blood–brain barrier seems advantageous for this purpose. Nanocarriers may also help to maintain the structure and function of TH, which is complex and unstable. Understanding how TH may interact with a nanocarrier is therefore cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Crucially, the stability of TH was maintained through loading and preserved during storage, and there was an increase in intracellular L-DOPA synthesis following NP uptake [145]. The same group also investigated the interactions between TH and a more modifiable and biodegradable NP, namely, porous silicon nanoparticles (pSiNPs) [146]. This study showed that the enzymatic activity of TH remained intact upon binding to the pSiNP surface, and pSiNPs could represent another promising device for therapeutic delivery of TH [146].…”
Section: Enzyme Replacement Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Crucially, the stability of TH was maintained through loading and preserved during storage, and there was an increase in intracellular L-DOPA synthesis following NP uptake [145]. The same group also investigated the interactions between TH and a more modifiable and biodegradable NP, namely, porous silicon nanoparticles (pSiNPs) [146]. This study showed that the enzymatic activity of TH remained intact upon binding to the pSiNP surface, and pSiNPs could represent another promising device for therapeutic delivery of TH [146].…”
Section: Enzyme Replacement Therapymentioning
confidence: 99%
“…The same group also investigated the interactions between TH and a more modifiable and biodegradable NP, namely, porous silicon nanoparticles (pSiNPs) [146]. This study showed that the enzymatic activity of TH remained intact upon binding to the pSiNP surface, and pSiNPs could represent another promising device for therapeutic delivery of TH [146]. This could potentially be achieved through intravenous injection, which would require pSiNP-bound TH to be stabilized during circulation followed by uptake into the brain by crossing the BBB.…”
Section: Enzyme Replacement Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…20 The Sailor group has spearheaded innovative research in using porous silicon ( pSi) as a matrix for substrate immobilization to assay enzyme activity. [21][22][23][24] The surface of pSi has been chemically modified to specifically adsorb a variety of substrates or enzymes, thereby enabling the construction of sensors tailored for particular enzymatic activities. Enzymatic activity is continuously monitored by observing the alterations in the optical properties of pSi throughout the enzyme-catalyzed reactions.…”
Section: Introductionmentioning
confidence: 99%